Using active systems to control tunnel fire events - Carvel,R; Colella,F; Rein,G (Proceedings of the Institution of Civil Engineers Engineering and Computational Mechanics, 2012)
Catastrophic tunnel fires are rare events, but often with large economic impacts. Current fire safety strategies for fire events in tunnels are generally designed on the basis of a large fire, overlooking the fact that every large fire starts as a small fire and some small fires may be controlled. This paper looks at ventilation and suppression systems and the extent to which these systems can control fire behaviour at each stage in the fire growth chain. Informed implementation of ventilation systems in the early and growth stages of a fire can significantly decrease the rate of fire growth, while careless use of ventilation may lead to rapid fire growth. Suppression systems are generally able to slow the rate of growth of a fire but, in many instances, it is not possible to reduce the size of a fire using such systems, even if they do generally prevent fire spread to adjacent vehicles. It is proposed that for maximum fire control during an incident in a tunnel, ventilation systems are used carefully in the initial stages of a fire, while suppression systems, if available, may be used in the rapid growth phase. The proposed fire control measures may rely on a level of detection and monitoring that is not currently possible in tunnels, but which should be available in the foreseeable future.